Including security mechanisms into systems architecture supporting vulnerabilities - Abad Espinoza, M. (2010)
The development of information systems and their construction must be ever more efficient, they must present a detailed analysis in relation to security. Thus, it must integrate security mechanisms during the stages of analysis and construction, these mechanisms may have a different arrangement according to how they are used. Then the security mechanisms will be integrated according to its nature the information system depending on the architecture defined for this. © 2010 IEEE.